Tổng hợp vật liệu thủy tinh hoạt tính sinh học 50S bằng phương pháp sol-gel. Nghiên cứu thực nghiệm ‘‘in vitro’’ - Vương, Bùi Xuân (Vietnam Journal of Chemistry, 2017)
A bioactive glass with composition 50SiO2 - 35CaO -15P2O5 (wt%) (noted 50S) was elaborated by the sol-gel method. ‘‘In vitro’’ bioactivity of this glass was evaluated by soaking of glass-powder samples in a simulated body fluid (SBF). XRD and SEM methods were used to evaluate the phisico-chemical properties of material before and after the ‘‘in vitro’’ test. Obtained rerults showed the bioactivity of this glass by the formation of a bioactive hydroxyapatite (HA) layer on its surface. This apatite layer has a similar chemical composition with the mineral phase of human bone. It allows a chemical bonding between bio-implant and natural bone. Consequently, the bone architecture is repaired and restored. Keywords. Bioactive glass, bioactivity, hydroxyapatite, ‘‘in vitro’’, sol-gel.